Development of an Internet of Things-Based Garbage Collection Robot - Putri Liana; Rahmat Irsyada; Roihatur Rohmah (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
The problem of garbage is not a new thing from the past until now, garbage is still the center of attention and a prolonged problem because of the various impacts of the problems that are caused and felt. Many factors are the cause of the increasing amount of garbage every day, including the lack of self-awareness about maintaining cleanliness and disposing of garbage in its place. This study aims to develop an IoT-based garbage collection robot. The method in developing this garbage collection robot is using the Fuzzy Mamdani method. The IoT-based garbage collection robot is designed using the Arduino Uno microcontroller as well as the Node MCU ESP 8266, HC-SR04 sensor, DHT11 sensor, SG90 Servo motor, DC motor and L298N motor driver. The way this robot works is to detect the distance with the HC-SR04 sensor as a distance data input then processed by the Arduino microcontroller and then the SG90 servo motor will move to clamp the garbage automatically and for the robot using control via a smartphone to be directed to the destination garbage. The results of this study are that the robot can clamp or pick up garbage with a distance of less than 5 cm and can control the speed of a DC motor using the fuzzy Mamdani method.